Perception of (In)Justice, Engagement, and Counterproductive Behavior in the Academic Environment: The Mediating Role of Emotions - Jelena Majcen; Iva Černja Rajter; Maša Tonković Grabovac (Psychological Topics, 2025)
The perception of (in)justice has become the subject of considerable scientific interest in the field of organizational psychology. In the academic environment, research has so far shown that the perception of justice is positively correlated with motivation and negatively correlated with anger and aggressive behavior toward teachers. However, less is known about the mechanisms of the various aspects of justice in an academic setting. The aim of this research was to provide a better understanding of justice perception in an academic context by (1) examining its connection to engagement and counterproductive behavior, and (2) viewing emotions as mediators of these relationships. A total of 426 students completed an online questionnaire comprising Teachers’ and Peers’ Fairness Scale, Affective Well-Being Scale for Students, Work Engagement Scale for Student Population, and Counterproductive Work Behavior Questionnaire for Student Population. Data analysis indicated a positive relationship between four dimensions of justice perception and engagement. Measures of counterproductive behavior showed a distinct pattern of connections with justice perception dimensions: only colleagues’ interactional justice was negatively correlated to interpersonal deviance, while teachers’ procedural and interactional fairness were negatively related to organizational deviance. Pleasant emotions accounted for a significant portion of variance in engagement across all dimensions of justice and mediated their relationships to engagement. Pleasant and unpleasant emotions did not show a unique contribution in predicting the dimension of counterproductive behavior above fairness. The results confirm the relevance of justice perceptions in the academic environment and provide guidelines for creating the environment conducive to fostering pleasant emotions and enhancing students’ engagement.